Financial markets' behavior around episodes of large changes in the fiscal stance - Silvia Ardagna (European Central Bank (ECB), 2004)
Using a panel of OECD countries from 1960 to 2002, this paper shows that financial markets value fiscal discipline. Interest rates, particularly those of long-term government bonds, decrease when countries' fiscal position improves and increase around periods of budget deteriorations. Stock market prices surge around times of substantial fiscal tightening and plunge in periods of very loose fiscal policy. In addition, the paper shows that results depend on countries' initial fiscal conditions and on the type of fiscal consolidations. Fiscal adjustments that occur in country-years with high levels of government defcit, that are implemented by cutting government spending, and that generate a permanent and substantial decrease in government debt are associated with larger reductions in interest rates and increases in stock market prices.
Keywords: E62; E44; H62; 330; fiscal expansions; Fiscal stabilizations; Interest Rates; stock market prices